Adherence to iron chelation therapy in patients who switched from deferasirox dispersible tablets to deferasirox film-coated tablets. (2nd November 2018) - Cheng, Wendy Y.; Said, Qayyim; Hao, Yanni; Xiao, Yongling; Vekeman, Francis; Bobbili, Priyanka; Duh, Mei Sheng; Nandal, Savita; Blinder, Morey
Abstract: Objective: To compare real-world adherence to and persistence with deferasirox film-coated tablets (DFX-FCT) and deferasirox dispersible tablets (DFX-DT) among patients who switched from DFX-DT to DFX-FCT, overall and by disease type (sickle cell disease [SCD], thalassemia, and myelodysplastic syndrome [MDS]). Methods: Patients were ≥2 years old and had ≥2 DFX-FCT claims over the study period and ≥2 DFX-DT claims before the index date (first DFX-FCT claim). The DFX-DT period was defined from the first DFX-DT claim to the index date; the DFX-FCT period was defined from the index date to the end of the study period. Adherence was measured as medication possession ratio (MPR) and proportion of days covered (PDC). Persistence was defined as continuous medication use without a gap ≥30 or 60 days between refills. Comparisons were conducted using paired-sample Wilcoxon sign-rank and McNemar's tests. Results: In total, 606 patients were selected (SCD: 348; thalassemia: 107; MDS: 106; other: 45). Adherence and persistence in the DFX-FCT vs DFX-DT period was significantly higher across all measures: mean MPR was 0.80 vs 0.76 ( p  < .001); 60.9% vs 54.3% of patients had MPR ≥ 0.8 ( p  = .009); mean 3-month PDC was 0.83 vs 0.71 ( p  < .001); 64.2% vs 45.4% of patients had 3-month PDC ≥ 0.8 ( p  < .001); 87.2% vs 63.4% of patients had 3-month persistence with no gap ≥30 days and 96.1% vs 79.9% with no gap ≥60 days ( p  < .001). Adherence and persistence improved after switching across all diseases, particularly MDS. Conclusions: Adherence and persistence improved significantly after switching from DFX-DT to DFX-FCT for all diseases, but especially MDS.